Implementasi Nilai - Nilai Pancasila dalam Penggunaan Media Sosial - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Ihsan Khoirul Anam; Hesti Arlinda Natasya; Rizquna Salsabila (Pusat Riset dan Inovasi Nasional, 2025)
Rapidly growing information and communication technology has significantly changed society, especially with the emergence of social media. In Indonesia, social media has become an important platform for connecting people and sharing information. However, as the use of social media increases, it is important to remember the moral values ​​that govern human interaction, as taught by Pancasila. This study applies a qualitative method based on literature studies from various sources, such as books, journals, and other media. This qualitative study aims to interpret the phenomena that occur around us and explain their influence on the values ​​of Pancasila in the use of social media. The results of the study show that Pancasila as the moral basis of the nation faces challenges from globalization and technological advances, especially in the use of social media. The noble values ​​contained in each principle are needed and applied in the digital life of society. The implementation of the values ​​of divinity, humanity, unity, democracy, and justice can be realized through a tolerant attitude, avoiding hoaxes and hate speech, maintaining social harmony, communicating wisely, and supporting equal access to information. Thus, social media can be a strategic means to strengthen national character and maintain Indonesian unity.